PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. SLS BEARINDO - Hotman Napitupulu (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2020)
Competition in the business world is getting tougher, companies are competing to find and improve the quality of their resources in order to achieve the desired goals of the company efficiently and effectively. This study aims to examine the effect of work discipline and motivation on the performance of employees of PT. SLS Bearindo. The analytical method used is quantitative analysis using primary data by distributing questionnaires given to PT.SLS Bearindo employees with a sample of 92 employees. The data analysis technique used is multiple linear regression analysis. The results showed a positive and significant effect simultaneously between work discipline and motivation on employee performance. partially between work discipline on employee performance has a significant effect and between motivation on employee performance has a significant effect.